Buck-Buck the chicken - Ehrlich, Amy, 1942-; Alley, R. W. (Robert W.) (New York : Random House, 1987)
Nancy$1 (Bs pet chicken Buck-Buck has trouble learning to act like an ordinary chicken.s
D., unk, c2000
Keywords: Chickens -- Fiction; Pets -- Fiction; Humorous stories